2009
DOI: 10.1038/sj.bjc.6605448
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of pertuzumab in combination with trastuzumab in uterine serous papillary adenocarcinoma

Abstract: BACKGROUND: Uterine serous papillary adenocarcinoma (USPC) is a rare but highly aggressive variant of endometrial cancer. Pertuzumab is a new humanised monoclonal antibody (mAb) targeting the epidermal growth factor type II receptor (HER2/neu). We evaluated pertuzumab activity separately or in combination with trastuzumab against primary USPC cell lines expressing different levels of HER2/neu. METHODS: Six USPC cell lines were assessed by immunohistochemistry (IHC), flow cytometry, and real-time PCR for HER2/n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 32 publications
6
93
0
Order By: Relevance
“…ADCC activity is one of the key mechanisms of the antitumor activity of trastuzumab (36). Moreover, recent reports showed that pertuzumab also had ADCC activity (19,37). Antiangiogenic activity is also shown as the mechanism of antitumor activity of trastuzumab (12).…”
Section: Discussionmentioning
confidence: 99%
“…ADCC activity is one of the key mechanisms of the antitumor activity of trastuzumab (36). Moreover, recent reports showed that pertuzumab also had ADCC activity (19,37). Antiangiogenic activity is also shown as the mechanism of antitumor activity of trastuzumab (12).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have demonstrated that trastuzumab results in antibody-dependent cellular cytotoxicity in the range of 25% to 60% against HER2-overexpressing USC, which can be augmented by both IL-2 and simultaneous administration of the heterodimerization inhibitor pertuzumab (Omnitarg, Genentech). 58,59,70 Recent case reports also showed evidence of in vivo clinical activity of trastuzumab in patients with advanced or recurrent endometrial carcinoma. 53,71,72 However, no significant activity was observed in the GOG-181B phase II trial of singleagent trastuzumab in advanced or recurrent endometrial carcinoma patients.…”
Section: Her2 Amplification and Overexpressionmentioning
confidence: 99%
“…Overexpression of these glycoproteins exists in most tumor cells and will promote tumor cell proliferation and their resistance to therapy. For example, overexpression of HER1 was found in 40% of gliomas (Wong et al 1992), while overexpression of HER2 occurs in most breast cancer cells (EI-Sahwi et al 2010). Based on the fact that the expression level of EGFR was different (mostly higher) in tumor cells compared to that in normal cells, the inhibition of EGFRs expression and their related signal transduction pathways will prevent cancer cells proliferation and their survival.…”
Section: Introductionmentioning
confidence: 98%